2022
DOI: 10.1001/jamanetworkopen.2022.26208
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Parent Income and Education, Neighborhood Disadvantage, and Child Brain Structure

Abstract: Key Points Question What are the associations of parent or caregiver educational attainment, income-to-needs ratio, and neighborhood disadvantage (and their interactions) with brain structure in children? Findings In this cross-sectional study of 8862 children aged 9 to 10 years, different indicators of socioeconomic status (SES) had distinct correlations with children’s brain structure. Thus, high income-to-needs ratios may play a protective role in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 84 publications
(175 reference statements)
4
31
0
Order By: Relevance
“…Cognitive performance also likely has both social (i.e., school, family) and neurobiological (i.e., brain-supported functioning) foundations that would position cognition as either a contributor to or consequence of brain development [26][27][28] , and future research may dissociate these effects using more specific measurements. Additionally, because morphometry in certain regions connected to the SLF (e.g., superior frontal-parietal cortices), CST (e.g., precentral gyrus), and Fmaj (e.g., occipital lobes) has similarly exhibited associations with SES and cognition in children [12][13][14]28,30,32,33 , our findings in white matter might reflect developmental interactions with gray matter instead of an isolated process 71 .…”
Section: Discussion (1167 Words)mentioning
confidence: 84%
See 1 more Smart Citation
“…Cognitive performance also likely has both social (i.e., school, family) and neurobiological (i.e., brain-supported functioning) foundations that would position cognition as either a contributor to or consequence of brain development [26][27][28] , and future research may dissociate these effects using more specific measurements. Additionally, because morphometry in certain regions connected to the SLF (e.g., superior frontal-parietal cortices), CST (e.g., precentral gyrus), and Fmaj (e.g., occipital lobes) has similarly exhibited associations with SES and cognition in children [12][13][14]28,30,32,33 , our findings in white matter might reflect developmental interactions with gray matter instead of an isolated process 71 .…”
Section: Discussion (1167 Words)mentioning
confidence: 84%
“…These studies used obesity measures as a proxy for diet and exercise 13 , and cognitive performance as a proxy for the social, sensory, and cognitive influence the brain, potentially through different pathways. Recent findings suggest that SES indicators at both neighborhood-level (e.g., area deprivation index) and household-level (e.g., income, parental education), though correlated, do independently relate to children's brain morphology and functional networks 12,13,[29][30][31][32][33] . In terms of SES, families having the same income level may have access to different neighborhoods due to differences in local cost of living and/or structural racism barriers 8 .…”
Section: Introduction (737 Words)mentioning
confidence: 99%
“…This could indicate that cortical thinning across childhood and adolescence might be affected more by genetic factors, while surface area (Strike et al, 2019) and GWC could be more sensitive to environmental impact. However, a recent paper by Rakesh et al (2022) reported associations between neighborhood disadvantage and local cortical thickness.…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies have linked specific measures of household SES to differences in youth behavior (Lahelma et al, 2006; Lorant et al, 2003; McLaughlin et al, 2011) and brain structure (Lawson et al, 2013; Noble et al, 2015, 2012; Rakesh et al, 2022), but little is known about household-level SES-related effects on brain predicted aging. Herein, we show that our previously derived SES and psychopathology-blind brain age metrics (Zhao et al, 2019) are in fact associated with specific components of household SES and anxiety/depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Lower SES has also been shown to associate with lower global white matter volumes in one study (McDermott et al, 2019) but not in others (Jednoróg et al, 2012; Mackey et al, 2015). In line with differing associations between SES components and mental health outcomes, parent education and income differ in their ability to predict cortical thickness across the brain (Lawson et al, 2013; Noble et al, 2015, 2012; Rakesh et al, 2022) as well as hippocampal volume (Noble et al, 2015). These findings suggest different SES components may be biologically distinct and could help explain how SES components result in divergent mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%